2013
DOI: 10.1097/mnm.0b013e328360d945
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between 18F-FDG metabolic volumetric parameters and clinicopathological factors of breast cancer

Abstract: TLG may reflect tumor metabolism for clinicopathological factors of breast cancer better than SUV(max) or MTV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 14 publications
4
25
2
1
Order By: Relevance
“…On the basis of our previous findings 1 5 , we hypothesized that an acidity biomarker should have two characteristics. First, as the rate of glycolysis increases with breast cancer progression, this should also lead to an association of progression with acidity 11 38 . Hence, a biomarker of acidosis should increase with stage.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of our previous findings 1 5 , we hypothesized that an acidity biomarker should have two characteristics. First, as the rate of glycolysis increases with breast cancer progression, this should also lead to an association of progression with acidity 11 38 . Hence, a biomarker of acidosis should increase with stage.…”
Section: Resultsmentioning
confidence: 99%
“…Our Institutional Review Board approved the retrospective chart review (2014-04-027-002). The inclusion criteria were verification of primary IDC and ALN metastasis by histological evaluation, preoperative FDG PET/CT for clinical staging, and tumors >1 cm in pathologic size based on full-width at half maximum (FWHM) of PET [ 13 14 15 ]. Patients who had bilateral breast cancers and those who had received neoadjuvant chemotherapy or radiotherapy before surgery were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…However, the relationship between SUV max and clinicopathological factors of breast cancer is diverse and has not been entirely elucidated. Kaida et al [37] performed studies on PET volumetric parameters in patients with breast carcinoma and concluded that MTV and TLG are related to certain clinicopathological factors of breast carcinoma. By comparing three different quantification parameters, they showed that TLG showed better tumor metabolism for those isolated clinicopathological factors of breast carcinoma than SUV max or MTV.…”
Section: Feature Definition Descriptionmentioning
confidence: 99%